2012
DOI: 10.1038/onc.2011.660
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic screen of human DNA repair genes identifies aberrant promoter methylation of NEIL1 in head and neck squamous cell carcinoma

Abstract: Aberrant promoter methylation of different DNA repair genes has a critical role in the development and progression of various cancer types, including head and neck squamous cell carcinomas (HNSCCs). A systematic analysis of known human repair genes for promoter methylation is however missing. We generated quantitative promoter methylation profiles in single CpG units of 160 human DNA repair genes in a set of DNAs isolated from fresh frozen HNSCC and normal tissues using MassARRAY technology. Ninety-eight perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 47 publications
5
30
0
Order By: Relevance
“…Going forward, it seems reasonable that besides defining the repair capacity of the canonical interstrand crosslink responses, namely the NER factors XPF/ERCC1 and homologous recombination (22), the levels of DNA glycosylases should be considered when predicting patient responsiveness to crosslinking drugs used in the clinic. Significantly, NEIL1 protein levels and activity have been shown to be altered (primarily decreased) in cancer cells, due to both genetic and epigenetic factors (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Going forward, it seems reasonable that besides defining the repair capacity of the canonical interstrand crosslink responses, namely the NER factors XPF/ERCC1 and homologous recombination (22), the levels of DNA glycosylases should be considered when predicting patient responsiveness to crosslinking drugs used in the clinic. Significantly, NEIL1 protein levels and activity have been shown to be altered (primarily decreased) in cancer cells, due to both genetic and epigenetic factors (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NEIL1 has also been reported to have the ability to regulate the mutation frequency in mammalian cells (Maiti et al, 2008). In regard to genetic alterations in human malignancies, somatic NEIL1 mutations associated with reduced repair activity of the mutant protein in gastric cancer and reduced NEIL1 expression in cancers of the head and neck, lung, and colorectum have been reported, suggesting that the reduced NEIL1 repair activity associated with such alterations may contribute to increased malignant potential of the cells (Shinmura et al, 2004;Chaisaingmongkol et al, 2012;Do et al, 2014;Farkas et al, 2014). Recently, a list of Japanese germline variants was published in the website of the Japanese Human Genetic Variation Database (HGVD) (http:// www.genome.med.kyoto-u.ac.jp/SnpDB) (Narahara et al, 2014), and we found the c.C844T NEIL1 variant, which results in the production of the p.Q282Stop-type protein, in the database.…”
Section: Introductionmentioning
confidence: 97%
“…Alterations in DNA methylation status are associated with many biological processes, including wound healing and fibrosis, [29][30][31][32] DNA repair, 33,34 cell cycle regulation, [35][36] inflammatory/stress response, 37,38 apoptosis, and tumorigenesis. 39 DNA methylation at the 5 position of cytosine within CpG dinucleotides epigenetically controls gene expression and maintains genome integrity.…”
mentioning
confidence: 99%